Comparison of [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG Uptake in Esophageal Cancer - Liu, Huipan; Hu, Zhi; Yang, Xiao; Dai, Tianyang; Chen, Yue (Frontiers in Oncology, 2022)
Purpose: Accurate clinical staging is crucial to managing esophageal cancer. [68Ga]Ga-DOTA-FAPI-04 exhibits good diagnostic performance in various tumors, showing a promising alternative to [18F]FDG. Here, we investigated the diagnostic performance of [68Ga]Ga-DOTA-FAPI-04 PET/CT and [18F]FDG PET/CT in the diagnosis of primary and metastatic lesions of esophageal cancer. Methods: Patients with esophageal cancer who underwent concurrent [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT between January 2020 and June 2021 were retrospectively analyzed. [68Ga]Ga-DOTA-FAPI-04 and [18F]FDG PET/CT uptakes were compared by using the paired samples t test. The McNemar test was used to compare the diagnostic performance between the two techniques. Results: Thirty-five patients [median age, 63.5 years old (range, 44–83 years old)] were evaluated in our study. In treatment-naive patients (n=25), [68Ga]Ga-DOTA-FAPI-04 PET could detect all esophageal cancers, whereas 1 patient with superficial esophageal cancer was negative in FDG but positive in [68Ga]Ga-DOTA-FAPI-04 (T1). [68Ga]Ga-DOTA-FAPI-04 uptake was higher than [18F]FDG in primary lesions (13.8±6.9 vs 10.9±6.8, respectively, P=0.004), involved lymph nodes (9.3±5.2 vs 6.4±5.9, respectively, P=0.002), and bone and visceral metastases (10.4±6.0 vs. 6.1±7.5, respectively, P=0.001). In addition, [68Ga]Ga-DOTA-FAPI-04 PET/CT has a higher detection sensitivity than [18F]FDG PET/CT for primary tumors (100% [25/25] vs 96.0% [24/25], respectively), lymph nodes (95.0% [57/60] vs 75.0% [45/60], P<0.001), and bone and visceral metastases (100% [25/25] vs 72% [18/25], respectively; P= 0.008). Conclusion: [68Ga]Ga-DOTA-FAPI-04 PET/CT has higher tracer uptake value and is superior to [18F]FDG PET/CT in detecting primary and metastatic lesions in patients with esophageal cancer.